Treatment for morbid obesity. Issue 879 (1st January 1999) - Carmichael, A R
Abstract : There is no single unifying theory to explain the aetiology of obesity but several environmental factors, such as decreased physical activity and increased fat intake may contribute to its development in genetically predisposed individuals. Dietary and pharmacological treatments of morbid obesity have been proven to be unsuccessful. Modern surgical treatments have been shown to be effective in achieving significant weight loss with consequent reduction in morbidity. Despite the fact that surgical treatment of morbid obesity is the only therapeutic form that has stood the test of time, it still remains a crisis-driven form of therapy in the UK. It is probable that a better understanding of the aetiology and physiology of obesity may lead to the development of an effective pharmacological treatment of obesity in the future. However, until then, surgical treatment of morbid obesity should be considered as an effective and efficient way of treatment in selected cases.